2014
DOI: 10.1002/btpr.1890
|View full text |Cite
|
Sign up to set email alerts
|

Advanced near‐infrared monitor for stable real‐time measurement and control of Pichia pastoris bioprocesses

Abstract: Near‐infrared spectroscopy is considered to be one of the most promising spectroscopic techniques for upstream bioprocess monitoring and control. Traditionally the nature of near‐infrared spectroscopy has demanded multivariate calibration models to relate spectral variance to analyte concentrations. The resulting analytical measurements have proven unreliable for the measurement of metabolic substrates for bioprocess batches performed outside the calibration process. This paper presents results of an innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Goldfeld et al [26] have recently evaluated the use of an NIR device for real-time monitoring and control of a Pichia pastoris bioprocess. Six fermentations took place in 1.6-and 3-l reactors.…”
Section: On-linementioning
confidence: 99%
“…Goldfeld et al [26] have recently evaluated the use of an NIR device for real-time monitoring and control of a Pichia pastoris bioprocess. Six fermentations took place in 1.6-and 3-l reactors.…”
Section: On-linementioning
confidence: 99%
“…Using an instrumentation system that employs a proprietary signal processing algorithm, it was shown that NIR can be used to monitor glycerol, methanol, and biomass concentration in the fermentation of Pichia pastoris . The accuracy of the on‐line measurement allowed its use in the controlled methanol feeding to maintain its concentration at a low level . A challenge of using NIR for nutrient concentration measurement is the extensive experimentation and data analysis development effort needed to make the system work.…”
Section: Sensors Commonly Used In Bioprocessmentioning
confidence: 99%
“…Saccharomyces cerevisiae is the most widely used yeast in alcoholic fermentation because Correspondance: Dr. María Guadalupe Aguilar-Uscanga (gaguilar@itver.edu.mx), Bioengineering Laboratory, Food Research and Development Unit, Veracruz Institute of Technology, Av. Development and bioprocess optimization are highly dependent on accurate real-time monitoring of chemical and physical process variables [11][12][13]. Some investigators have published studies using xylose-fermenting recombinant S. cerevisiae strains to solve this problem [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%